Robotic surgery in the aspect of liver transplantation - K. O. Semash (Трансплантология (Москва), 2024)
Introduction. Almost 60 years have passed since the first liver transplant performed by Thomas Starzl. During this time, medical technologies have gradually improved, which has made it possible to use more and more new methods and approaches in this type of medical care. One of the new techniques of recent decades is robotic surgery, which is gradually being introduced into medical practice, including in the field of transplant medicine.Objective. The purpose of writing this review was to summarize knowledge and describe the current status of development of robotic surgery in the aspect of liver transplantation, namely: liver resection in donors, as well as graft implantation in the recipient.Material and methods. The review includes foreign and domestic publications on minimally invasive donor liver surgery. Publications on the topic of robotic liver resection in the aspect of liver transplantation were also processed.Conclusion. Robotic surgery using advanced robotic systems represents the next step in the development of minimally invasive technologies in liver transplantation. Robotic systems provide more precise and dexterous control of instruments, allowing surgeons to perform complex procedures with greater precision and less risk to patients. However, the robotic approach is still very limited in geographical distribution and requires much more experience than laparoscopy. The upcoming introduction of new robotic systems that support haptic feedback or cavitronic ultrasonic surgical aspirators will further promote a widespread adoption of robotic liver resection in liver donors and liver recipients.